Glaciological problems set by control of dangerous lakes in Cordillera Blanca, Peru. I. Historical failures of Morainic dams, their causes and prevention - Lliboutry, Louis (1977)
The retreat of glaciers since 1927 in Cordillera Blanca has produced dangerous lakes on the front of many glaciers. All the known data, most of them unpublished, are reviewed. The known aluviones are listed, and those of Chavin, Quebrada Los Cedros and Artesoncocha described in full. In these three cases a breach in the front mo ra ine came from big ice falls into the lake. The protective d evices made on the outlets are described, as well as the effects of the big earthquake on 31 May 1970. In the case of Laguna Parón, which keeps its level thanks to infiltrations, the flu ctuations of the discharge of the springs as related to the level of the lake from 1955 to 1969 are reported. The projects for lowering the level of Laguna Parón and for emptying Safuna Alta are described. The latter partially emptied in fact by piping after the earthquake, allowing a final solution.